2017
DOI: 10.3390/s17071666
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Source Linear Energy Prediction (LINE-P) Model in the Context of WSNs

Abstract: Energy harvesting technologies such as miniature power solar panels and micro wind turbines are increasingly used to help power wireless sensor network nodes. However, a major drawback of energy harvesting is its varying and intermittent characteristic, which can negatively affect the quality of service. This calls for careful design and operation of the nodes, possibly by means of, e.g., dynamic duty cycling and/or dynamic frequency and voltage scaling. In this context, various energy prediction models have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…In [ 5 ] the authors presented three cases of LINE-P (linear energy prediction model) that are based on the sampling and approximation theory. The authors showed that LINE-P (all cases) is more accurate, has a lower complexity, and is energy-efficient in terms of computation as compared to other non-adaptive EP models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [ 5 ] the authors presented three cases of LINE-P (linear energy prediction model) that are based on the sampling and approximation theory. The authors showed that LINE-P (all cases) is more accurate, has a lower complexity, and is energy-efficient in terms of computation as compared to other non-adaptive EP models.…”
Section: Methodsmentioning
confidence: 99%
“…In this article, we first briefly recall the limitations of most existing EP models due to the fixed-weighting parameter issue; thereafter, we suggest a solution with an adaptive weighting factor based on the energy profiles. In [ 5 ], we discussed how most of the energy prediction models such as EWMA, WCMA, ASEA, PRO-Energy, QL-SEP, and LINE-P (all cases) are dependent on a fixed weighting parameter; however, these solutions are not always suitable for real implementations with many various types (and hence characteristics) of e.g., solar energy harvesters.…”
Section: Introductionmentioning
confidence: 99%
“…Many different prediction models have been proposed in recent years. Most of them use energy observations in prior days to predict future energy availability: QL-SEP [6], EWMA [7], WCMA [8], ASEA [9], Pro-Energy [10,11], IPro-Energy [12], SEPCS [13], UD-WCMA [14], LINE-P [15], and Adaptive LINE-P [16]. This class of models requires maintaining locally collected data about the energy harvested during a number of prior days.…”
Section: Related Workmentioning
confidence: 99%
“…We will provide a more detailed description of Pro-Energy and UD-WCMA in the following subsections. SEPCS [13] and LINE-P [15] employ complex linear prediction models that take into account both previous energy samples from the same day and energy samples from previous days. Finally, Adaptive LINE-P [16] improves LINE-P with adaptive weighting parameters.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation